Agrarian Law Reform in the Context of Climate Change and Food Security - Judijanto, Loso; Lubis, Mitra Musika; Intes, Amina; Rahayu, Ninik Sri; Suparwata, Dewa Oka (Rechtsnormen: Journal of Law, 2024)
Background: Climate change poses significant challenges to global food security, exacerbating issues such as land degradation, water scarcity, and crop yield variability. Agrarian law reform has the potential to enhance resilience and sustainability in agricultural practices, thereby improving food security. However, the existing agrarian legal frameworks in many countries are not adequately equipped to address the impacts of climate change. Objective: This study aims to analyze the role of agrarian law reform in enhancing food security in the context of climate change. The research seeks to identify legal gaps and propose reforms that can facilitate adaptive and sustainable agricultural practices, ensuring stable food production and distribution. Methods: A qualitative research design was employed, utilizing document analysis and comparative legal analysis. The study examined existing agrarian laws, policies, and international agreements related to climate change and food security. Data were collected from legal texts, policy documents, and reports from various countries and international organizations. Expert interviews with legal scholars, policymakers, and agricultural practitioners were conducted to gather insights on effective legal frameworks and practices. Results: The analysis revealed significant gaps in current agrarian laws regarding climate adaptation and sustainable agricultural practices. Key issues identified include inadequate land tenure security, insufficient legal support for sustainable farming techniques, and lack of integration between agrarian laws and climate policies. into their agrarian legal frameworks. Conclusion: The study concludes that comprehensive agrarian law reform is essential for enhancing food security in the face of climate change. Recommendations include strengthening land tenure security